DETERMINANTS ANALYSIS OF NON PERFORMING LOAN USING BANK SPECIFIC VARIABLES AND MACROECONOMIC FACTORS OF 19 COMMERCIAL BANKS IN INDONESIA - Putra, Reynold Adi; Anggono, Achmad Herlanto (Journal of Business and Management, 2017)
Abstract. Bank’s main activity in generating income is by spreading credit. The credit given by the bank might become Non Performing Loan (NPL), which is a condition when the interest payment is delayed by the agreement. Thus, credit risk is one of the most important risk that are faced by the bank. This research intended to find the relationship of banks specific variables: Bank Size (LNSIZE), Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Return on Asset (ROA) and Net Interest Margin (NIM) and macroeconomic factors: Inflation Rate (INFL), Interest Rate (INTR) and Growth Domestic Product (LNGDP) toward Non Performing Loan (NPL) in 19 commercial banks in Indonesia which is included in BACB 3 and 4 in the period of 2012-2016. The data is processed using panel data regression with Random Effect Method. The result shows that CAR, LDR, NIM and LNGDP have positive significant relationship to NPL while LNSIZE and ROA have negative significant relationship to NPL. On the other hand, INFL and INTR have no significant relationship to NPL. According to the result, the author recommend commercial banks in Indonesia to be more careful in spreading the credit using the funds that have been generated by the bank to improve the credit quality and monitor the significant variable so the amount of NPL can be decreased. Keywords: Non Performing Loan, Bank Specific Variables, Macroeconomic Factors, Indonesia.